Political-Cultural Analysis of Organizations - Lucas, Rob (Academy of Management Review, 1987)
The political conception of organizations that emerged in the i970s revised conventional understanding of organization structure and process. Scholars using the cultural approach in the 1980s are attempting a similar type of reconceptualization. By incorporating the subgroup unit of analysis which is characteristic of political approaches, a more intelligible account of the structure and process which produce the outcomes of organizational behavior may be constructed. The conceptual basis of a political-cultural analysis and a methodology for implementing such an analysis based on the structural anthropology of Levi-Strauss are described.